Data mining in electronic commerce using classification technique / Lim Lee Chin - Lim , Lee Chin (2003)
This thesis project is carried out in order to fulfill one of the academic requirements for Bachelor of Computer Science from University of Malaya. The project involved the development of Data mining in electronic commerce using classification technique. Firstly, this report will cover the general concept of data mining, project motivation objectives of data mining, scope of project, current limitation and an expected outcome and project schedule. Secondly, this report will review the literature. This part will cover basic knowledge of data mining system. Then followed by introducing data mining techniques and tools. Methodology part also will be discussed in chapter III. In the system analysis, it is about analysis of functions and non-functional requirements specification. Next part is system design that describes the data flow of my system. The final part of my project is system implementation and testing. It is description of the environment in which the systems are developed and implemented after completion. It also includes verifications and validations of the system to make sure the errors in the minimum level.